(untitled) (Bangladesh Journal of Anatomy, 2016)
Context: The extra hepatic biliary ducts include the right and left hepatic ducts, common hepatic duct and common bile duct. The luminal diameter of the biliary ducts gradually increase with age but it may dilate significantly in obstructive disease in the biliary passage. A variety of factors have been reported to have an effect on the size of the biliary ducts, such as dislodged calculi from the gallbladder, history of prior cholecystectomy, congenital abnormalities or anatomical variations. Ultimately, the luminal size should be considered as a single part of the entire assesment of the biliary tree. However, such an assesment implies knowledge of the normal size of the biliary passage. Materials and Methods: A cross sectional descriptive type of study was carried out in the department of Anatomy, Sir Salimullah Medical College on sixty two (62) human cadaveric extra hepatic biliary apparatus. The samples were collected from unclaimed dead bodies that were under examination in the department of Forensic Medicine of Dhaka Medical College, Dhaka and Sir Salimullah Medical College, Dhaka. The present study was conducted to determine the normal luminal diameter of extra hepatic biliary ducts histologically and their age related changes. Results: The differences in mean (±SD) luminal diameter of the cystic duct, common hepatic duct and common bile duct were found statistically significant (P<0.001) between different age groups. Conclusion: In the present study the luminal diameter of the extra hepatic biliary duct was found to increase with advancing age. Bangladesh Journal of Anatomy January 2016, Vol. 14, No. 1, pp. 1-4